Postpancreatectomy Acute Pancreatitis (PPAP): Definition and Grading From the International Study Group for Pancreatic Surgery (ISGPS). Issue 4 (29th April 2022) - Marchegiani, Giovanni; Barreto, Savio George; Bannone, Elisa; Sarr, Michael; Vollmer, Charles M.; Connor, Saxon; Falconi, Massimo; Besselink, Marc G.; Salvia, Roberto; Wolfgang, Christopher L.; Zyromski, Nicholas J.; Yeo, Charles J.; et al.
Abstract : Objective: The ISGPS aimed to develop a universally accepted definition for PPAP for standardized reporting and outcome comparison. Background: PPAP is an increasingly recognized complication after partial pancreatic resections, but its incidence and clinical impact, and even its existence are variable because an internationally accepted consensus definition and grading system are lacking. Methods: The ISGPS developed a consensus definition and grading of PPAP with its members after an evidence review and after a series of discussions and multiple revisions from April 2020 to May 2021. Results: We defined PPAP as an acute inflammatory condition of the pancreatic remnant beginning within the first 3 postoperative days after a partial pancreatic resection. The diagnosis requires (1) a sustained postoperative serum hyperamylasemia (POH) greater than the institutional upper limit of normal for at least the first 48 hours postoperatively, (2) associated with clinically relevant features, and (3) radiologic alterations consistent with PPAP. Three different PPAP grades were defined based on the clinical impact: (1) grade postoperative hyperamylasemia, biochemical changes only; (2) grade B, mild or moderate complications; and (3) grade C, severe life-threatening complications. Discussions: The present definition and grading scale of PPAP, based on biochemical, radiologic, and clinical criteria, are instrumental for a better understanding of PPAP and the spectrum of postoperative complications related to this emerging entity. The current terminology will serve as a reference point for standard assessment and lend itself to developing specific treatments and prevention strategies.